2017
DOI: 10.1016/j.str.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual Site Phosphorylation of Caspase-7 by PAK2 Blocks Apoptotic Activity by Two Distinct Mechanisms

Abstract: Caspases, the cysteine proteases that execute apoptosis, are tightly regulated via phosphorylation by a series of kinases. Although all apoptotic caspases work in concert to promote apoptosis, different kinases regulate individual caspases. Several sites of caspase-7 phosphorylation have been reported, but without knowing the molecular details, it has been impossible to exploit or control these complex interactions, which normally prevent unwanted proliferation. During dysregulation, PAK2 kinase plays an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…There has been some suggestion in the literature that in vitro phosphorylation of kinase substrates sometimes differs from cellular phosphorylation (21,30,31). We have not previously observed irregular phosphorylation of caspase substrates by any of the kinases we have studied (19,32,60). Once again in this work, we found that in vitro phosphorylation by c-Abl accurately reflected the intracellular phosphorylation specificity we observed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…There has been some suggestion in the literature that in vitro phosphorylation of kinase substrates sometimes differs from cellular phosphorylation (21,30,31). We have not previously observed irregular phosphorylation of caspase substrates by any of the kinases we have studied (19,32,60). Once again in this work, we found that in vitro phosphorylation by c-Abl accurately reflected the intracellular phosphorylation specificity we observed.…”
Section: Discussionsupporting
confidence: 80%
“…This fidelity between in vitro and cell-based observations is probably due to casp-9 being a direct substrate of c-Abl. Our data from multiple kinase-caspase pairs suggest that when the appropriate kinase is studied, in vitro and cellular phosphorylation patterns are conserved (19,32,60).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Caspases have numerous substrates and often rely on exosites to maintain specificity. 41,42,55 It is possible that a zinc-binding site on caspase-3 could disrupt critical protein-protein interactions and limit substrate accessibility or even redirect hydrolysis towards particular proteins of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The data reveal that, like caspase-3, the mutations at this conserved site in caspases-6 and -7 also had no significant effect on the activity of these enzymes (Table 1). We note that a recent study by Hardy and coworkers showed similar results for a comparable variant of caspase-7, that of T173E (34). In addition to introducing phospho-mimetic mutations, we removed the salt-bridge between E176 and R271' in caspase-7 by replacing E176 with glycine, either individually or in combination with the T173D phospho-mimetic.…”
Section: Evolutionary Conservation Of Helix-3 Cterminal Loopmentioning
confidence: 53%